Intermittent Hemiplegia in a Boy with Primary Moyamoya Disease: A Case Report from Iran - BIDAKI, Reza; ZAREPUR, Ehsan (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Bidaki R, Zarepur E. Intermittent Hemiplegia in A Boy With Primary Moyamoya Disease; A Case Report from Iran. Iran J Child Neurol. Spring 2017; 11(2):65-68. Abstract Moyamoya is a rare chronic progressive occlusive cerebrovascular disease. Its manifestation varies from stroke, progressive learning impairment and transient ischemic attack to headache and seizure. There is no accepted medical treatment and surgery usually, is needed. We report here a case of 8 yr old boy referred to psychiatrist outpatient. An eight yr old boy with intermittent hemiplegia was brought to Imam Ali Clinic, Yazd, Iran in 2015 because his headache and medical problem began from 6 yr old. Stress and excitement exacerbated his condition. His first attack was at the age of 6 yr old. During attack, he had incontinence, severe headache, alogia, pallor, claudication and left hemiplegia (Left lower limb). Magnetic resonance angiography (MRA) was done and our diagnosis was moyamoya disease. Moyamoya is a mysterious disease and psychiatrists should consider it in differential diagnosis of alogia and plegia. Acute management of this disease is mainly symptomatic. Nowadays, surgery is a good choice and early diagnosis of this disease can change our patient’s life. References 1. Hallemeier CL, Rich KM, Grubb RL, Chicoine MR, Moran CJ, Cross DT, et al. Clinical features and outcome in North American adults with moyamoya phenomenon. Stroke 2006;37(6):1490-6. 2. Suzuki J, Takaku A. Cerebrovascular “moyamoya” disease. Disease showing abnormal net-like vessels in base of brain. Arch Neurol 1969;20(3):288-99. 3. Wakai K, Tamakoshi A, Ikezaki K, Fukui M, Kawamura T, Aoki R, et al. Epidemiological features of moyamoya disease in Japan: findings from a nationwide survey. Clin Neurol Neurosurg 1997;99 Suppl 2:S1-5. 4. Duan L, Bao XY, Yang WZ, Shi WC, Li DS, Zhang ZS, et al. Moyamoya disease in China: its clinical features and outcomes. Stroke 2012;43(1):56-60. 5. Im SH, Cho CB, Joo WI, Chough CK, Park HK, Lee KJ, et al. Prevalence and epidemiological features of moyamoya disease in Korea. J Cerebrovasc Endovasc Neurosurg 2012;14(2):75-8. 6. Lutterman J, Scott M, Nass R, Geva T. Moyamoya syndrome associated with congenital heart disease. Pediatrics 1998;101(1 Pt 1):57-60. 7. Peerless SJ. Risk factors of moyamoya disease in Canada and the USA. Clin Neurol Neurosurg 1997;99 Suppl 2:S45-8. 8. Abuzayed B, Khreisat W, Maaiah W, Agailat S. Supratentorial primitive neuroectodermal tumor presenting with intracranial hemorrhage in adult. J Neurosci Rural Pract 2014;5(2):176-9. 9. Yamauchi T, Houkin K, Tada M, Abe H. Familial occurrence of moyamoya disease. Clin Neurol Neurosurg 1997;99 Suppl 2:S162-7. 10. Kim JS. Moyamoya Disease: Epidemiology, Clinical Features, and Diagnosis. J Stroke 2016;18(1):2-11. 11. Smith ER, Scott RM. Surgical management of moyamoya syndrome. Skull Base 2005;15(1):15-26. 12. Yamada I, Suzuki S, Matsushima Y. Moyamoya disease: comparison of assessment with MR angiography and MR imaging versus conventional angiography. Radiology 1995;196(1):211-8. 13. Nakakita K, Tanaka S, Fukuda A, Fujii C, Kohama A, Miyasato H. [Nontraumatic acute subdural hematoma caused by the rupture of transdural anastomotic vessels in moyamoya disease]. No Shinkei Geka 1994;22(6):561-5. 14. Mughal DK, Nissirios KS, Puri MR. A 30-Year-Old Female with Moyamoya Disease and Associated Depression. Psychiatr Ann 2014;44(12):549-551. 15. Kim T, Oh CW, Bang JS, Kim JE, Cho WS. Moyamoya Disease: Treatment and Outcomes. J Stroke 2016;18(1):21-30.